Entropy optimization and response surface methodology of blood hybrid nanofluid flow through composite stenosis artery with magnetized nanoparticles (Au-Ta) for drug delivery application - Algehyne, Ebrahem A.; Ahammad, N. Ameer; Elnair, Mohamed E.; Zidan, Mohamed; Alhusayni, Yasir Y.; El-Bashir, B. O.; Saeed, Anwar; Alshomrani, Ali Saleh; Alzahrani, Faris (Scientific reports, 2023)
Entropy creation by a blood-hybrid nanofluid flow with gold-tantalum nanoparticles in a tilted cylindrical artery with composite stenosis under the influence of Joule heating, body acceleration, and thermal radiation is the focus of this research. Using the Sisko fluid model, the non-Newtonian behaviour of blood is investigated. The finite difference (FD) approach is used to solve the equations of motion and entropy for a system subject to certain constraints. The optimal heat transfer rate with respect to radiation, Hartmann number, and nanoparticle volume fraction is calculated using a response surface technique and sensitivity analysis. The impacts of significant parameters such as Hartmann number, angle parameter, nanoparticle volume fraction, body acceleration amplitude, radiation, and Reynolds number on the velocity, temperature, entropy generation, flow rate, shear stress of wall, and heat transfer rate are exhibited via the graphs and tables. Present results disclose that the flow rate profile increase by improving the Womersley number and the opposite nature is noticed in nanoparticle volume fraction. The total entropy generation reduces by improving radiation. The Hartmann number expose a positive sensitivity for all level of nanoparticle volume fraction. The sensitivity analysis revealed that the radiation and nanoparticle volume fraction showed a negative sensitivity for all magnetic field levels. It is seen that the presence of hybrid nanoparticles in the bloodstream leads to a more substantial reduction in the axial velocity of blood compared to Sisko blood. An increase in the volume fraction results in a noticeable decrease in the volumetric flow rate in the axial direction, while higher values of infinite shear rate viscosity lead to a significant reduction in the magnitude of the blood flow pattern. The blood temperature exhibits a linear increase with respect to the volume fraction of hybrid nanoparticles. Specifically, utilizing a hybrid nanofluid with a volume fraction of 3% leads to a 2.01316% higher temperature compared to the base fluid (blood). Similarly, a 5% volume fraction corresponds to a temperature increase of 3.45093%.